Reversible Inhibition of Tomato Fruit Gene Expression at High Temperature (Effects on Tomato Fruit Ripening). - Lurie, S. (1996)
The reversible inhibition of three ripening-related processes by high-temperature treatment (38[deg]C) was examined in tomato (Lycopersicon esculentum L. cv Daniella) fruit. Ethylene production, color development, and softening were inhibited during heating and recovered afterward, whether recovery took place at 20[deg]C or fruit were first held at chilling temperature (2[deg]C) after heating and then placed at 20[deg]C. Ethylene production and color development proceeded normally in heated fruit after 14 d of chilling, whereas the unheated fruit had delayed ethylene production and uneven color development. Levels of mRNA for 1-aminocyclopropane-1-carboxylic acid oxidase, phytoene synthase, and polygalacturonase decreased dramatically during the heat treatment but recovered afterward, whereas the mRNA for HSP17 increased during the high-temperature treatment and then decreased when fruit were removed from heat. As monitored by western blots, the HSP17 protein disappeared from fruit tissue after 3 d at 20[deg]C but remained when fruit were held at 2[deg]C. The persistence of heat-shock proteins at low temperature may be relevant to the protection against chilling injury provided by the heat treatment. Protein levels of 1-aminocyclopropane-1-carboxylic acid oxidase and polygalacturonase also did not closely follow the changes in their respective mRNAs. This implied both differences in relative stability and turnover rates of mRNA compared to protein and nontranslation of the message that accumulated in low temperature. The results suggest that high temperature inhibits ripening by inhibiting the accumulation of ripening-related mRNAs. Ripening processes that depend on continuous protein synthesis including ethylene production, lycopene accumulation, and cell-wall dissolution are thereby diminished.